2021
DOI: 10.1136/annrheumdis-2021-eular.3942
|View full text |Cite
|
Sign up to set email alerts
|

Ab0800 hematological Markers of Systemic Inflammation in Patients Rheumatoid Arthritis (Ra) and Spondyloarthritis (Spa)

Abstract: Background:An appropriate assessment of disease activity is essential in the management of patients with chronic inflammatory joint diseases, rheumatoid arthritis (RA) and spondyloarthritis (SpA). Hematological parameters [Neutrophil-To-Lymphocyte (NLR), Platelet-To-Lymphocyte (PLR) and Monocyte-To- Lymphocyte (MLR) ratios] have been demonstrated to be good, promising indicators of systemic inflammation status in different diseases, additionally to conventional inflammatory markers [erythrocyte sedimentation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies have revealed the association between elevated platelets, platelet indices [Platelet Lymphocyte Ratio (PLR), Platelet Distribution Width (PDW) and Mean Plate Volume (MPV)], neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR) and eosinophil-to-lymphocyte (ELR) ratio with inflammation (Pogorzelska et al, 2020;Zhou et al, 2020;López-Verdugo et al, 2020, Targonska et al, 2021. These haematological parameters have been identified as sensitive markers of occult inflammation and disease activity for many diseases including systemic lupus erythematosus, rheumatoid arthritis, psoriasis, and oesophageal cancer (López-Verdugo et al, 2020;Pornchai and Ratanapha, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the association between elevated platelets, platelet indices [Platelet Lymphocyte Ratio (PLR), Platelet Distribution Width (PDW) and Mean Plate Volume (MPV)], neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR) and eosinophil-to-lymphocyte (ELR) ratio with inflammation (Pogorzelska et al, 2020;Zhou et al, 2020;López-Verdugo et al, 2020, Targonska et al, 2021. These haematological parameters have been identified as sensitive markers of occult inflammation and disease activity for many diseases including systemic lupus erythematosus, rheumatoid arthritis, psoriasis, and oesophageal cancer (López-Verdugo et al, 2020;Pornchai and Ratanapha, 2019).…”
Section: Discussionmentioning
confidence: 99%